Does “Kamishibai” (Picture-story show) improve children's behaviors and learning in pre-primary education?: Evidence from Madagascar - Takao Maruyama; Kengo Igei (International Journal of Educational Research Open)
While universal quality pre-primary education is a global agenda, the shortage of qualified teachers and teaching materials is a major challenge in low-income countries. In Madagascar, the proportion of teachers with minimum required qualification in pre-primary education is less than half. To improve the quality of pre-primary education, the Ministry of Education in Madagascar piloted a set of interventions, including teacher training and the distribution of Kamishibai, a simple picture-story show for children. This study investigated whether Kamishibai changed children's behaviors and learning using a randomized controlled trial. The experiment targeted senior-class pupils (five to six years old) in 14 public pre-primary activity centers. The results of the experiment showed that Kamishibai improved children's behaviors of hygiene, understanding of security, responsibility, and autonomy. Kamishibai also enhanced their foundational literacy and numeracy. The results of this study suggest that it is possible to improve the quality of pre-primary education with simple teaching materials in the challenging context of a low-income country.